2020
DOI: 10.1101/2020.05.19.105338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical probe-based Nanopore Sequencing to Selectively Assess the RNA modifications

Abstract: RNA modifications contribute to RNA and protein diversity in eukaryotes and lead to amino acid substitutions, deletions, and changes in gene expression levels. Several methods have developed to profile RNA modifications, however, a less laborious identification of inosine and pseudouridine modifications in the whole transcriptome is still not available. Herein, we address the first step of the above question by sequencing synthetic RNA constructs with inosine and pseudouridine modification using Oxford Nanopor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…The Ψ sites were spaced >25 nt apart to study them one at a time as they pass from the helicase to the nanopore sensor, an overall distance that spans ~17 nt from the entry of the helicase to the exit of the kmer sensing zone in the protein nanopore. Pseudouridine is base called by Guppy predominantly as U or C, consistent with other studies, 26 and the present work found the ratio is dependent on the local sequence context (Figure 2). The base-calling error for Ψ was greater than U permitting detection of the modification (Figure 3); however, the base-calling errors were sequence context dependent, similar to the base-calling differences.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The Ψ sites were spaced >25 nt apart to study them one at a time as they pass from the helicase to the nanopore sensor, an overall distance that spans ~17 nt from the entry of the helicase to the exit of the kmer sensing zone in the protein nanopore. Pseudouridine is base called by Guppy predominantly as U or C, consistent with other studies, 26 and the present work found the ratio is dependent on the local sequence context (Figure 2). The base-calling error for Ψ was greater than U permitting detection of the modification (Figure 3); however, the base-calling errors were sequence context dependent, similar to the base-calling differences.…”
Section: Discussionsupporting
confidence: 93%
“…When Ψ was present, the nucleotide called was predominantly a mixture of C and U and a low amount of A or G, consistent with prior results. [26][27][28] The new finding herein is the distribution of C and U called at the 13 singly-modified Ψ sites ranged from 10% to 97% C with the remainder predominantly called as U (Figure 2A). Inspection of the sequencedependent base calling results for Ψ did not lead to an obvious sequence context trend.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…has demonstrated the feasibility of this approach. 28 , 29 Sequencing of the 16s rRNA from E. coli with the MinION successfully called m 7 G and Ψ at known sites; 30 additionally, m 6 A and Ψ have been found by base-calling errors in tRNA at known sites, synthetic mRNA, and mRNA from cellular sources. 29 , 31 34 While many Ψ sites were identified in the prior studies, our analysis revealed that many sites would be missed on samples with Ψ at unknown locations.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review described in details the RNAseq based approaches [31]. Noteworthy, the very recent development of single molecule direct RNA sequencing method by Oxford Nanopore Technologies (ONT, Oxford, UK), is promising for the analysis of modification landscape on a specific RNA sequence, including Ψs [48][49][50][51].…”
Section: Technological Advances: Detecting Rna Modificationsmentioning
confidence: 99%